High-performance industrial alkaline electrolytic water hydrogen evolution electrode and laser direct writing preparation method thereof
By combining electrodeposition and laser direct writing technology on nickel foam, the CoP/Co2P catalytic electrode with multi-stage pore structure was synthesized in situ, which solved the poor activity and insufficient stability of the cobalt-based phosphide hydrogen evolution cathode under large electric density conditions. Problem, high activity and long life of industrial alkaline electrolytic hydrogen-analyzed electrodes are achieved.
Patent Information
- Application Number
- CN202411658326.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-10-28
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-18
AI Technical Summary
The existing cobalt-based phosphide hydrogen evolution cathode has poor activity and insufficient stability under large electric density conditions, resulting in high energy consumption and short service life of industrial alkaline electrolytes.
Constant current electrode deposition in cobalt nitrate solution was used to obtain electrodeposited nickel foam, and after soaking in ammonium phosphate solution, CoP with multi-stage pore structure was synthesized in situ by laser direct writing technology. /Co2P composite catalytic electrode.
It improves the alkaline HER activity of the catalyst and the stability under large electric density conditions, reduces the energy consumption and production cost of the electrode, and is suitable for large-scale industrial production.
Smart Images

Figure CN119465273A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalysis, and in particular relates to a high-performance industrial alkaline water electrolysis hydrogen evolution electrode and a laser direct writing preparation method thereof. Background Art
[0002] With the development of society and the increase of population, the demand for energy is becoming more and more huge, the rapid consumption of fossil fuels and the increasingly serious environmental problems, the development of renewable, clean and efficient energy is essential to achieve sustainable development of all mankind. Hydrogen is one of the ideal green energy sources in the future due to its green, high calorific value and renewable characteristics.
[0003] Compared with traditional methods such as steam methane reforming and coal gasification, hydrogen production by water electrolysis has the advantages of being green, clean and having high product purity, and is one of the ideal methods for hydrogen production. At present, hydrogen production by alkaline water electrolysis is a mature industrial method for producing green hydrogen. The electrodes used in its cathode hydrogen evolution reaction (HER) are usually prepared by coating highly active nickel-based catalysts (such as Raney nickel, etc.) powder on nickel foam or nickel mesh. However, this catalytic electrode has the problems of poor activity at high current density and easy detachment of the powdered catalyst, resulting in high energy consumption and short life of industrial alkaline electrolyzers. To address this challenge, it is necessary to conduct in-depth research and adopt more advanced electrode preparation technologies to develop new catalytic electrodes with high activity and high catalytic stability that can meet the needs of industrial equipment.
[0004] Pt-based catalysts exhibit excellent alkaline HER activity, but their high cost and scarce reserves limit their large-scale application. Transition metal phosphides (TMPs) have suitable H adsorption free energy and unique electronic structure. P atoms can extract electrons from metal atoms and capture positively charged protons, thus exhibiting excellent HER activity. See: Esfandiari N, Aliofkhazraei M, Colli AN, et al. Prog. Mater. Sci., 2024, 144, 101254. Among them, cobalt-based phosphides are widely used in the field of alkaline HER. However, pure phase cobalt-based phosphides are limited by the number of active sites and charge transfer rate, and their alkaline HER activity is still inferior to that of precious metals.
[0005] Studies have shown that TMPs rich in metal-metal bonds and metal-phosphorus bonds exhibit better electron transfer efficiency, thermal stability and chemical stability than TMPs rich in phosphorus-phosphorus bonds. Therefore, by adjusting the ratio of metal to phosphorus and properly combining the surface of the catalyst with the reaction intermediates, the alkaline HER activity of cobalt-based phosphides can be improved. Liu et al. successfully prepared a heterostructure composed of CoP and Co2P. Due to the strong electronic coupling of the built-in electric field at the heterojunction, the transfer of electrons from CoP to Co2P was effectively promoted, making the H adsorption free energy at the P site closer to 0, greatly improving the alkaline HER activity of the catalyst. See: Liu BS, Zhong B, Li F, et al. Nano Res., 2023, 16(11), 12830-12839.
[0006] Vacancy engineering is an effective modification strategy that is widely used in the study of electrocatalytic HER, because vacancies can effectively change the electronic structure of the catalytic site and thus optimize the adsorption energy of the intermediate. 12 The construction of P vacancies in P5 greatly improves the alkaline HER activity of the catalyst. Experimental and theoretical results show that P vacancies weaken the hybridization of Ni 3d and P 2p orbitals, promote the desorption process of H*, and accelerate the reaction kinetics of alkaline HER. See: Duan JJ, Chen S, Ortiz-Ledon CA, et al. Angew Chem. Int, Edit., 2020, 59(21), 8181-8186.
[0007] In addition, for industrial alkaline electrolyzed water, it is often necessary to reach ≥500mA / cm 2The current density is high, so the high-density activity and stability of the catalytic electrode are crucial for industrial applications. It is mainly limited by the conductivity of the catalyst, the number of active sites and the mass transfer capacity, so special material structure design is required to meet the needs of industrial applications. See: Luo Y T, Zhang ZY, Chhowalla M, et al. Adv. Mater., 2022, 34 (16), 2108133. Many studies have shown that constructing a porous structure can effectively improve the high-density activity of the catalyst. On the one hand, the porous structure provides more active sites, and on the other hand, it ensures the transmission of the electrolyte and the rapid desorption of hydrogen bubbles under high current and strong gasification conditions, thereby ensuring the mass transfer capacity. See: Li W, Liu J, Guo PF, et al. Adv. Energy Mater., 2021, 11 (42), 2102134. Ao WD, Ren HJ, Cheng CG, et al. Angew Chem. Int, Edit., 2023, 62 (30), 2305158. Yao Y, Zhu YH, Pan CQ, et al.J.Am.Chem.Soc.,2021,143(23),8720-8730.
[0008] It can be seen that if a CoP / Co2P composite structure rich in P vacancies with a porous structure can be synthesized, an industrial cathode catalyst with excellent alkaline HER catalytic activity can be obtained. However, the synthesis of such a composite system is undoubtedly complex and difficult, and it is difficult to achieve using conventional chemical synthesis methods, so there is currently no report on the relevant material structure. Summary of the invention
[0009] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a high-performance industrial alkaline water electrolysis hydrogen evolution electrode and a laser direct writing preparation method thereof.
[0010] To achieve the above object, the technical solution adopted by the present invention is:
[0011] A laser direct writing preparation method for a high-performance industrial alkaline water electrolysis hydrogen evolution electrode comprises the following steps: 1) using a three-electrode system to perform constant current electrodeposition in a cobalt nitrate solution to obtain electrodeposited nickel foam; 2) soaking the electrodeposited nickel foam in an ammonium phosphate solution; 3) performing laser direct writing on the soaked nickel foam obtained in step 2) to obtain a high-activity industrial alkaline water electrolysis hydrogen evolution electrode.
[0012] In step 1), the three-electrode system comprises nickel foam as the working electrode, a carbon rod as the counter electrode, and a saturated calomel electrode as the reference electrode; preferably, the nickel foam is ultrasonically cleaned in deionized water and anhydrous ethanol, respectively, and then immersed in dilute hydrochloric acid to remove the surface oxide layer.
[0013] The concentration of the cobalt nitrate solution in step 1) is 0.05-1M, preferably 0.05-0.2M; more preferably 0.2M.
[0014] In step 1), the electrodeposition current density is -5 to -100 mA / cm 2 , preferably -50mA / cm 2 ; The deposition time is 100 to 1200 s; preferably 100 to 600 s; more preferably 600 s.
[0015] In step 2), the concentration of the ammonium phosphate solution is 0.1-3M, and the immersion time is 5-60min; preferably, the concentration of the ammonium phosphate solution is 0.6M, preferably, the immersion time is 5-20min, and more preferably 20min.
[0016] The laser direct writing setting parameters in step 3) are: using a pulsed laser with a wavelength of 1064nm, a laser energy of 0.2 to 10J, and a scanning speed of 2 to 20mm / s; the preferred laser energy is 0.2 to 3J, more preferably 3J; the laser scanning rate is 2 to 10mm / s, more preferably 10mm / s.
[0017] The invention comprises a high-performance industrial alkaline water electrolysis hydrogen evolution electrode obtained by the preparation method, 10mA / cm 2 The hydrogen evolution overpotential at current density is 31~56mV; 1000mA / cm 2 The hydrogen evolution overpotential under current density is 145~186mV.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] The purpose of the present invention is to address the current industrial technical problems of high electrical density activity and poor stability of cobalt-based phosphide hydrogen evolution cathodes, and to provide a method combining electrodeposition with laser direct writing technology on nickel foam to in-situ synthesize a CoP / Co2P integrated catalytic electrode rich in P vacancies with a multi-level pore structure.
[0020] On the one hand, the present invention effectively optimizes the adsorption and cracking of water molecules and the adsorption and desorption of H by pure phase cobalt-based phosphides in the alkaline HER process through the technical strategy of vacancy engineering and heterogeneous interface engineering, accelerates its reaction kinetics, and improves the intrinsic catalytic activity. On the other hand, by constructing a multi-level pore structure, the number of active sites is increased, while the circulation of electrolyte and the desorption of hydrogen bubbles are promoted, thereby improving the catalytic activity under high-current density conditions.
[0021] The present invention is the first to use millisecond laser direct writing technology to achieve a catalyst control strategy of morphology control, vacancy engineering and heterogeneous interface engineering coupling, effectively solving the industrial technical problem of poor alkaline HER activity of cobalt-based phosphides, and proposing a method for synthesizing an integrated catalytic electrode for high-activity industrial hydrogen evolution. In addition, this synthesis method is simple in process, easy to operate, easy to control, has excellent product performance, and does not use toxic reaction raw materials. It is an environmentally friendly green synthesis process that can efficiently prepare large-area electrodes and is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 A process diagram for in-situ synthesis of cobalt-based phosphide catalytic electrodes with phosphorus vacancies and hierarchical pore structures by millisecond laser direct writing;
[0023] Figure 2 The phase and morphology characterization diagrams of the cobalt-based phosphide catalytic electrode (L-CoxP / NF-1) with a multi-level pore structure and rich in phosphorus vacancies obtained in Example 1, and the cobalt-based phosphide catalytic electrode (H-CoxP / NF) without a multi-level pore structure and phosphorus vacancies obtained in Comparative Example 1. (a) is the X-ray diffraction (XRD) spectrum of Example 1 and Comparative Example 1; (b) is the electron paramagnetic resonance (EPR) spectrum of Example 1 and Comparative Example 1; (cf) are scanning electron microscope (SEM) images of Example 1 at different magnifications;
[0024] Figure 3 The cobalt-based phosphide catalytic electrode (L-Co x Figure 1 shows the structural characterization of nanoparticles P / NF-1. (a) is a transmission electron microscope (TEM) image, and the inset is a statistical histogram of nanoparticle size; (b) is a selected area electron diffraction (SAED) spectrum; (c) is a high-resolution transmission electron microscope (HR-TEM) image; (d) is a dark field scanning transmission electron microscope (HADDF-STEM) image; (d1-d3) are energy dispersive X-ray surface distribution (EDS) images of different elements.
[0025] Figure 4 The cobalt-based phosphide catalytic electrode (L-Co x P / NF-1), the cobalt-based phosphide catalytic electrode (H-Co x The performance comparison of water electrolysis hydrogen production of commercial cobalt phosphide (CoP / NF), cobaltous phosphide (Co2P / NF) and platinum carbon catalyst (Pt / C / NF) coated on nickel foam. (a) is the polarization curve of hydrogen evolution reaction; (b) is the comparison of overpotential under different current densities; (c) is the performance comparison of commercial cobalt phosphide (CoP / NF), cobaltous phosphide (Co2P / NF) and platinum carbon catalyst (Pt / C / NF) coated on nickel foam.x P / NF-1 at 1000mA / cm 2 The chronoamperometric curve of the reaction for 1000 h at the current density. (d) L-Co in Example 1 x Comparison of polarization curves of P / NF-1 before and after stability reaction.
[0026] Figure 5 To control the parameters of the electrodeposition step, the parameters of the immersion step in ammonium phosphate solution and the laser direct writing step parameters are used to obtain the performance comparison of hydrogen production by electrolysis of water of Examples 1-13. (a) Polarization curves of hydrogen evolution reaction of Example 1 and Examples 2-5; (b) Polarization curves of hydrogen evolution reaction of Example 1 and Examples 6-9; (c) Polarization curves of hydrogen evolution reaction of Example 1 and Examples 10-13. DETAILED DESCRIPTION
[0027] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and the best embodiments.
[0028] Embodiment 1:
[0029] Laser direct writing method for preparing high performance industrial alkaline water electrolysis hydrogen evolution electrode, using a device such as Figure 1 As shown in the figure, 1: millisecond laser; 2: nickel foam; 3: asbestos board; 4: electric translation stage.
[0030] The steps include:
[0031] (1) Cut a 25×20 mm nickel foam and ultrasonically clean it in deionized water and anhydrous ethanol for 18 min, then soak it in 3M dilute hydrochloric acid for 10 min, take it out and repeatedly clean it with deionized water and dry it;
[0032] (2) dissolving cobalt nitrate in 50 mL of deionized water to obtain a 0.2 M cobalt nitrate electroplating solution; using a three-electrode system for electrodeposition, with the nickel foam obtained in step (1) as the working electrode, the carbon rod as the counter electrode, and the saturated calomel electrode as the reference electrode, and setting the deposition current to -50 mA / cm 2 , the deposition time is 600s. After the deposition is completed, the nickel foam is taken out, washed with deionized water and then dried;
[0033] (3) soaking the electrodeposited nickel foam obtained in step (2) in a 0.6 M ammonium phosphate solution for 20 min, then taking it out and drying it directly;
[0034] (4) Fixing the nickel foam obtained in (3) on an asbestos board, and directly writing the electrode in air at room temperature using a millisecond laser equipped with an electric translation stage, setting the direct writing range to 18×20 mm, the laser scanning rate to 10 mm / s, and the laser energy to 3 J through the control software and the laser control panel;
[0035] (5) After the laser direct writing is completed, the nickel foam obtained in step (4) is cleaned with deionized water and dried to obtain a cobalt-based phosphide catalytic electrode with a multi-level pore structure and rich in phosphorus vacancies;
[0036] (6) The sample obtained in Example 1 is denoted as L-Co x P / NF-1.
[0037] The results of the physical and morphological characterization of Example 1 are shown in Figure 2 . Figure 2 a is the XRD spectrum of Example 1, and its characteristic diffraction peaks match those of Co2P (PDF#54-0413) and CoP (PDF#29-0497), proving that its phase is a mixed phase of Co2P and CoP. Figure 2 b is the EPR spectrum of Example 1, which has an obvious P vacancy characteristic peak, proving that a high concentration of P vacancy defects exists in the material. Figure 1 cf are SEM images of Example 1 at different magnifications, which have the morphological characteristics of a multi-level pore (quaternary) structure, in which the maximum pore size can reach a macropore size of >10 μm and the minimum pore size is a mesopore size of <50 nm.
[0038] The microstructure characterization results of Example 1 are shown in Figure 3 . Figure 3 This is a structural representation diagram of Example 1. Figure 3 (a) is a TEM image of Example 1, and its microscopic morphology is nanoparticles with an average particle size of about 5.7 nm. Figure 3 (b) Figure 3 (a) SAED spectrum of the area, where the radii of the diffraction rings on different crystal planes match those of Co2P and CoP. Figure 3 (c) HR-TEM image of Example 1, where the interplanar spacing belongs to single crystalline nanoparticles of Co2P and CoP. Figure 3 (d) and Figure 2 (d1-d3) are the HADDF-STEM images and EDS surface distribution diagrams of Example 1, in which Co and P elements are evenly distributed, and the element ratio is about Co:P = 3:2. The above characterization results prove that Example 1 is a Co2P / CoP composite catalyst rich in P vacancies with a multi-level pore structure.
[0039] Example 1 The LSV polarization curve of hydrogen evolution tested in 1M KOH solution is shown in Figure 4a, the comparison of overpotentials at different current densities is shown in Figure 4 b. It can be seen that its 10mA / cm 2 , 500mA / cm 2 and 1000mA / cm 2 The hydrogen evolution overpotentials under current density were 31mV, 133mV and 145mV respectively, which were better than commercial Pt / C, Co2P and CoP catalysts, showing outstanding intrinsic activity and high current density activity. In addition, the catalytic stability of Example 1 was analyzed. Figure 4 cd is Example 1 at 1000 mA / cm 2 The long-term chronoamperometric curve under current density and the LSV curve before and after the stability test show that the performance has almost no attenuation after 1000h of testing, demonstrating excellent high current density hydrogen evolution stability.
[0040] Comparative Example 1:
[0041] (1) Cut a 25×20 mm nickel foam and ultrasonically clean it in deionized water and anhydrous ethanol for 10 min, then soak it in 2M dilute hydrochloric acid for 15 min, take it out and repeatedly clean it with deionized water and dry it;
[0042] (2) Dissolve 0.2 M cobalt nitrate in 50 mL of deionized water to obtain an electroplating solution; use a three-electrode system for electrodeposition, with the nickel foam obtained in step (1) as the working electrode, the carbon rod as the counter electrode, and the saturated calomel electrode as the reference electrode, and set the deposition current to -50 mA / cm 2 , the deposition time is 600s. After the deposition is completed, the nickel foam is taken out, washed with deionized water and then dried;
[0043] (3) soaking the electrodeposited nickel foam obtained in step (2) in a 0.6 M ammonium phosphate solution for 30 min, then taking it out and drying it directly;
[0044] (4) annealing the nickel foam obtained in (3) at 350° C. for 3 hours in an argon atmosphere to obtain a cobalt-based phosphide catalytic electrode free of a multi-level pore structure and phosphorus vacancies;
[0045] (5) The sample obtained in Comparative Example 1 is denoted as H-Co x P / NF.
[0046] The results of the physical phase and defect structure characterization of Comparative Example 1 are shown in Figure 2 . Figure 2 a is the XRD spectrum of comparative example 1, and its diffraction characteristic peak is consistent with that of example 1, proving that its phase is a mixed phase of Co2P and CoP. Figure 2b is the EPR spectrum of comparative example 1, in which no characteristic peak exists, proving that there is no P vacancy defect in the material. The LSV polarization curve of hydrogen evolution tested in 1M KOH solution for comparative example 1 is shown in Figure 4 a, the comparison of overpotentials at different current densities is shown in Figure 4 b. It can be seen that its 10mA / cm 2 , 500mA / cm 2 and 1000mA / cm 2 The hydrogen evolution overpotentials under current density were 75mV, 194mV and 207mV, respectively, which were better than commercial Co2P and CoP catalysts, but the activity was lower than that of Example 1. This result shows that the activity of the composite structure catalyst of Co2P and CoP is better than that of pure phase materials. On the other hand, it proves that the unique multi-level pore structure and P vacancy defects obtained by laser direct writing can further improve the alkaline hydrogen evolution performance of the composite structure, especially under high current density conditions.
[0047] Embodiment 2:
[0048] The basic steps are as described in Example 1, except that the concentration of cobalt nitrate in step (2) is 0.05 M. The sample obtained in Example 2 is denoted as L-Co x P / NF-2. Example 2 The LSV polarization curve of hydrogen evolution tested in 1M KOH solution is shown in Figure 5 a. It can be seen that its 10mA / cm 2 and 1000mA / cm 2 The hydrogen evolution overpotentials at the current densities are 38 mV and 155 mV, respectively.
[0049] Embodiment 3:
[0050] The basic steps are as described in Example 1, except that the concentration of cobalt nitrate in step (2) is 1 M. The sample obtained in Example 3 is denoted as L-Co x P / NF-3. Example 2 The LSV polarization curve of hydrogen evolution tested in 1M KOH solution is shown in Figure 5 a. It can be seen that its 10mA / cm 2 and 1000mA / cm 2 The hydrogen evolution overpotentials at the current densities are 75 mV and 223 mV, respectively.
[0051] Embodiment 4:
[0052] The basic steps are as described in Example 1, except that the deposition time in step (2) is 100 s. The sample obtained in Example 4 is denoted as L-Co x P / NF-4. Example 4 The LSV polarization curve of hydrogen evolution tested in 1M KOH solution is shown in Figure 5 a. It can be seen that its 10mA / cm2 and 1000mA / cm 2 The hydrogen evolution overpotentials at different current densities are 51 mV and 176 mV, respectively.
[0053] Embodiment 5:
[0054] The basic steps are as described in Example 1, except that the deposition time in step (2) is 1200 s. The sample obtained in Example 5 is denoted as L-Co x P / NF-5. Example 5 The LSV polarization curve of hydrogen evolution tested in 1M KOH solution is shown in Figure 5 a. It can be seen that its 10mA / cm 2 and 1000mA / cm 2 The hydrogen evolution overpotentials at the current densities are 94 mV and 254 mV, respectively.
[0055] Examples 2-5 studied the effect of the process parameters of the electrodeposition step on the hydrogen evolution performance of the catalyst. The LSV polarization curves of Examples 1 and 2-5 tested in 1M KOH solution are shown in Figure 5 a, it can be seen that the conditional parameters of the electroplating solution concentration and the electroplating time in the electroplating step have a significant effect on the catalytic activity of the catalyst. It mainly affects the mixed phase ratio in the final product and the corresponding alkaline HER activity by changing the thickness of the deposited layer. Specifically, the thicker the electroplating solution concentration, the longer the deposition time, and the thicker the surface catalyst precursor (cobalt hydroxide Co(OH)2) deposition layer. The thicker the deposition layer, the more difficult it is to completely phosphate in the subsequent phosphating step, resulting in most of the catalyst after phosphating being Co2P, and even unphosphated Co(OH)2, resulting in poor catalytic activity; on the contrary, the thinner the deposition layer, the more excessive phosphating, on the one hand, most of the final catalyst is CoP, on the other hand, the nickel foam substrate may be phosphated, resulting in reduced overall conductivity and poor catalytic performance. The final preferred electrodeposition parameters are: electroplating solution concentration 0.2M, deposition time 600s.
[0056] Embodiment 6:
[0057] The basic steps are as described in Example 1, except that the concentration of the ammonium phosphate solution in step (3) is 0.1 M. The sample obtained in Example 6 is denoted as L-Co x P / NF-6. Example 6 The LSV polarization curve of hydrogen evolution tested in 1M KOH solution is shown in Figure 5 b. It can be seen that its 10mA / cm 2 and 1000mA / cm 2 The hydrogen evolution overpotentials at different current densities are 71mV and 175mV, respectively.
[0058] Embodiment 7:
[0059] The basic steps are as described in Example 6, except that the concentration of the ammonium phosphate solution in step (3) is 3 M. The sample obtained in Example 7 is denoted as L-Co x P / NF-7. Example 7 The LSV polarization curve of hydrogen evolution tested in 1M KOH solution is shown in Figure 5 b. It can be seen that its 10mA / cm 2 and 1000mA / cm 2 The overpotentials for hydrogen evolution at different current densities are 80 mV and 221 mV, respectively.
[0060] Embodiment 8:
[0061] The basic steps are as described in Example 6, except that the immersion time in step (3) is 5 min. The sample obtained in Example 8 is recorded as L-Co x P / NF-8. The LSV polarization curve of hydrogen evolution tested in 1M KOH solution in Example 8 is shown in Figure 5 b. It can be seen that its 10mA / cm 2 and 1000mA / cm 2 The hydrogen evolution overpotentials at the current densities are 56 mV and 164 mV, respectively.
[0062] Embodiment 9:
[0063] The basic steps are as described in Example 6, except that the immersion time in step (3) is 60 min. The sample obtained in Example 9 is recorded as L-Co x P / NF-9. The LSV polarization curve of hydrogen evolution tested in 1M KOH solution in Example 9 is shown in Figure 5 b. It can be seen that its 10mA / cm 2 and 1000mA / cm 2 The hydrogen evolution overpotentials at different current densities are 105mV and 285mV, respectively.
[0064] Examples 6-9 studied the effect of the process parameters of ammonium phosphate solution immersion on the hydrogen evolution performance of the catalyst. The LSV polarization curves of Examples 1 and Examples 6-9 tested in 1M KOH solution are shown in Figure 5 a, it can be seen that the solution concentration and immersion time parameters have a significant effect on the catalytic activity of the catalyst. It mainly affects the mixed phase ratio in the final product and the corresponding alkaline HER activity by changing the degree of phosphating. Specifically, the higher the concentration of the ammonium phosphate solution, the longer the immersion time, the higher the degree of phosphating, and the final catalyst is mainly or entirely CoP; conversely, the lower the concentration of the ammonium phosphate solution, the shorter the immersion time, the lower the degree of phosphating, and the final catalyst is mainly Co2P, and even unphosphated Co(OH)2 exists. Figure 4As shown, the alkaline hydrogen evolution performance of pure phase CoP and Co2P is relatively poor, so the content of CoP and Co2P in the catalyst caused by the degree of phosphating affects the final activity. The final optimal parameters are: ammonium phosphate solution concentration 0.6M, immersion time 20min.
[0065] Embodiment 10:
[0066] The basic steps are as described in Example 1, except that the laser energy in step (4) is 0.2 J. The sample obtained in Example 10 is denoted as L-Co x P / NF-10. The LSV polarization curve of hydrogen evolution tested in 1M KOH solution in Example 10 is shown in Figure 5 c. It can be seen that its 10mA / cm 2 and 1000mA / cm 2 The hydrogen evolution overpotentials at the current densities are 48 mV and 164 mV, respectively.
[0067] Embodiment 11:
[0068] The basic steps are as described in Example 10, except that the laser energy in step (4) is 10 J. The sample obtained in Example 11 is denoted as L-Co x P / NF-11. The LSV polarization curve of hydrogen evolution tested in 1M KOH solution in Example 11 is shown in Figure 5 c. It can be seen that its 10mA / cm 2 and 1000mA / cm 2 The hydrogen evolution overpotentials at the current densities are 88 mV and 238 mV, respectively.
[0069] Embodiment 12:
[0070] The basic steps are as described in Example 10, except that the laser scanning rate in step (4) is 2 mm / s. The sample obtained in Example 12 is denoted as L-Co x P / NF-12. Example 12 The LSV polarization curve of hydrogen evolution tested in 1M KOH solution is shown in Figure 5 c. It can be seen that its 10mA / cm 2 and 1000mA / cm 2 The hydrogen evolution overpotentials at different current densities are 55mV and 186mV, respectively.
[0071] Embodiment 13:
[0072] The basic steps are as described in Example 10, except that the laser scanning rate in step (4) is 20 mm / s. The sample obtained in Example 13 is denoted as L-Co x P / NF-13. The LSV polarization curve of hydrogen evolution tested in 1M KOH solution in Example 13 is shown in Figure 5 c. It can be seen that its 10mA / cm 2 and 1000mA / cm 2 The hydrogen evolution overpotentials at different current densities are 71 mV and 202 mV, respectively.
[0073] Examples 10-13 studied the effect of laser direct writing process parameters on the hydrogen evolution performance of the catalyst. The LSV polarization curves of Examples 1 and Examples 10-13 tested in 1M KOH solution are shown in Figure 5 a, it can be seen that the laser energy and direct writing scanning rate have a significant effect on the catalytic activity of the catalyst. It mainly affects the mixed phase ratio in the final product and the corresponding alkaline HER activity by changing the pore size, pore density and P vacancy concentration of the multi-level pore structure. Specifically, the lower the laser energy, the higher the scanning rate, the smaller the single-point laser energy density, the multi-level pore structure is difficult to form, and the P vacancy content is small; conversely, the lower the laser energy, the higher the scanning rate, the greater the single-point energy density, the catalyst surface structure may be severely damaged, all resulting in poor catalytic activity. Therefore, the final preferred parameters are: laser energy 3J, laser scanning rate 10mm / s.
[0074] In summary, the purpose of the present invention is to address the current industrial technical problems of high electrical density activity and poor stability of cobalt-based phosphide hydrogen evolution cathodes, and to provide a method combining electrodeposition with laser direct writing technology on nickel foam to in situ synthesize a CoP / Co2P integrated catalytic electrode rich in P vacancies with a multi-level pore structure.
[0075] On the one hand, the present invention effectively optimizes the adsorption and cracking of water molecules and the adsorption and desorption of H by pure phase cobalt-based phosphides in the alkaline HER process through the technical strategy of vacancy engineering and heterogeneous interface engineering, accelerates its reaction kinetics, and improves the intrinsic catalytic activity. On the other hand, by constructing a multi-level pore structure, the number of active sites is increased, while the circulation of electrolyte and the desorption of hydrogen bubbles are promoted, thereby improving the catalytic activity under high-current density conditions.
[0076] The present invention is the first to use millisecond laser direct writing technology to achieve a catalyst control strategy of morphology control, vacancy engineering and heterogeneous interface engineering coupling, effectively solving the industrial technical problem of poor alkaline HER activity of cobalt-based phosphides, and proposing a method for synthesizing an integrated catalytic electrode for high-activity industrial hydrogen evolution. In addition, this synthesis method is simple in process, easy to operate, easy to control, has excellent product performance, and does not use toxic reaction raw materials. It is an environmentally friendly green synthesis process that can efficiently prepare large-area electrodes and is suitable for large-scale industrial production.
[0077] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A laser direct writing method for preparing a high-performance industrial alkaline water electrolysis hydrogen evolution electrode, characterized in that: The method comprises the following steps: 1) using a three-electrode system to perform constant current electrodeposition in a cobalt nitrate solution to obtain electrodeposited nickel foam; 2) soaking the electro-deposited nickel foam in an ammonium phosphate solution; 3) performing laser direct writing on the soaked nickel foam obtained in step 2) to obtain a high-activity industrial alkaline water electrolysis hydrogen evolution electrode.
2. The laser direct writing preparation method of the high-performance industrial alkaline water electrolysis hydrogen evolution electrode according to claim 1 is characterized in that: In step 1), the three-electrode system comprises nickel foam as the working electrode, a carbon rod as the counter electrode, and a saturated calomel electrode as the reference electrode; preferably, the nickel foam is ultrasonically cleaned in deionized water and anhydrous ethanol, respectively, and then immersed in dilute hydrochloric acid to remove the surface oxide layer.
3. The laser direct writing preparation method of the high-performance industrial alkaline water electrolysis hydrogen evolution electrode according to claim 1 is characterized in that: The concentration of the cobalt nitrate solution in step 1) is 0.05-1M, preferably 0.05-0.2M; more preferably 0.2M.
4. The laser direct writing preparation method of the high-performance industrial alkaline water electrolysis hydrogen evolution electrode according to claim 1 is characterized in that: In step 1), the electrodeposition current density is -5 to -100 mA / cm 2 , preferably -50mA / cm 2 ; The deposition time is 100 to 1200 s; preferably 100 to 600 s; more preferably 600 s.
5. The laser direct writing preparation method of the high-performance industrial alkaline water electrolysis hydrogen evolution electrode according to claim 1 is characterized in that: In step 2), the concentration of the ammonium phosphate solution is 0.1-3M, and the immersion time is 5-60min; preferably, the concentration of the ammonium phosphate solution is 0.6M, preferably, the immersion time is 5-20min, and more preferably 20min.
6. The laser direct writing preparation method of the high-performance industrial alkaline water electrolysis hydrogen evolution electrode according to claim 1 is characterized in that: The laser direct writing setting parameters in step 3) are: using a pulsed laser with a wavelength of 1064nm, a laser energy of 0.2 to 10J, and a scanning speed of 2 to 20mm / s; the preferred laser energy is 0.2 to 3J, more preferably 3J; the laser scanning rate is 2 to 10mm / s, more preferably 10mm / s.
7. A high-performance industrial alkaline water electrolysis hydrogen evolution electrode obtained by the preparation method according to any one of claims 1 to 6.
8. The high performance industrial alkaline water electrolysis hydrogen evolution electrode according to claim 7, characterized in that: 10mA / cm 2 The hydrogen evolution overpotential at current density is 31~56mV; 1000mA / cm 2 The hydrogen evolution overpotential under current density is 145~186mV.